Revisiting the tangled taxonomy of Scleria subgenus Scleria section Hymenolytrum: a lectotype replacement, a new synonym, and the reestablishment of Scleria cyperinoides as an accepted name - Layla Jamylle Costa Schneider; André Olmos Simões; Ana Cristina Andrade De Aguiar Dias; André Dos Santos Bragança Gil (Acta Botânica Brasílica, 2024)
Abstract During a taxonomic investigation of the names classified under Scleria subgenus Scleria section Hymenolytrum, it was necessary to replace the lectotype of S. macrogyne, as the specimen does not agree with the original description. In addition, we propose S. ramosa as a new synonym of S. macrogyne and discuss the reestablishment of S. cyperinoides as an accepted name.